A novel multipatient intranasal diamorphine spray for use in acute pain in children: pharmacovigilance data from an observational study. Issue 4 (9th January 2014) - Kendall, Jason; Maconochie, Ian; Wong, Ian C K; Howard, Richard; ,
Abstract : Objectives: To establish the safety of an intranasal diamorphine (IND) spray in children. Design: An open-label, single-dose pharmacovigilance trial. Setting: Emergency departments in eight UK hospitals. Participants: Children aged 2–16 years with a fracture or other trauma. Outcome measures: Adverse events (AE) specifically related to nasal irritation, respiratory and central nervous system depression. Results: 226 patients received 0.1 mg/kg IND. No serious or severe AEs occurred. The incidence of treatment-emergent AEs (TEAEs) was 26.5% (95% CI 20.9% to 32.8%), 93% being mild. 89% were related to treatment, all being known effects of the drug or route of administration except for three events in two patients. 20.4% (95% CI 15.3% to 26.2%) patients reported nasal irritation, all mild except one moderate and one 'unknown' severity. No respiratory depression was reported. Three AEs related to reduced Glasgow Coma Score (GCS) occurred, all mild. Conclusions: There were no safety concerns raised during the conduct of the study. In addition to expected side effects, IND can cause mild nasal irritation in a proportion of patients. European Union Drug Regulating Authorities Clinical Trial No: 2009-014982-16.